From rising water to floods: Disentangling the production of flooding as a hazard in Sumatra, Indonesia. Issue 118 (January 2021) - Merten, Jennifer; Nielsen, Jonas Østergaard; Rosyani,; Soetarto, Endriatmo; Faust, H.
Highlights: Risk research must increase our understanding of what is considered a hazard. Hazards (incl. floods) are the product of past and present socionatural relations. Relational approaches to risk and natural resources aid the study of hazards. In Jambi, Sumatra, land-use change alters the materiality and meaning of flooding. The prioritization of dry land for plantation development is a main driver of this. Abstract: In Jambi province, Sumatra, Indonesia, flooding is a recurrent rainy season phenomenon. Historically considered manageable, recent political economic developments have changed this situation. Today, flooding is an environmental hazard and a threat to people's livelihoods and health. Based on qualitative research and literature that has developed relational approaches to risk and water, we investigate past and present hydrosocial relations in Jambi province and reconstruct the changing meaning of flooding. We suggest that flooding as a hazard in Jambi was produced through the introduction of the plantation industry to the area and its prioritization of dry land for agro-industrial development. This development altered the materiality of water flows, reconfigured power relations and changed the socio-cultural dimensions of flooding. Together, these changes have led to a separation of flooding from its original social and geographic realm, producing new risks and vulnerabilities. This paper provides insights into the material and symbolic dimensions that influence how environmental processes come to be imagined, controlled and contested. It shows how tracing the socionatural production of hazards may help explain the increasingly systemic nature of risks and provide insights into the wider social meaning of environmental risks.